UPAYA MENINGKATKAN KUALITAS TIDUR PADA SISWA REMAJA SMA NEGERI 18 GARUT DENGAN BEROLAHRAGA - Arasy, Firdaus Abdul; Maulid, Ardy Syahrul; Muhimaturohmah, Siti; Akmal, Muhammad Rizki Nurul; Miftah, Yuda El (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2023)
This research is motivated by the large number of high school students who have poor sleep quality caused by the infrequent sports activities and poor physical condition due to readjustment to daily activities after the Covid-19 pandemic. In this regard, this study was made to see the influence between exercise habits and physical fitness in young students of SMA Negeri 18 Garut with their sleep quality and find out the efforts that can improve this. This study used a qualitative method, using an instrument in the form of a PSQI (Pittsburgh Sleep Quality Index) questionnaire using a Google Form with a quantitative descriptive analysis technique. The population in this study were 57 students at SMA Negeri 18 GARUT in the 2022/2023 academic year, which were later disallowed by 26 students so that the total subject became 31 students who were also the sample in this study. The technique used for sampling is random sampling. Based on the results of the study, it was found that the components of sleep quality and physical fitness were low, so that the correlation value between the two was bad. In conclusion, the level of physical fitness and exercise habits have a very influential relationship with the quality of adolescent sleep and vice versa.